Biofertilizer effect of yeast fermented broth on organic tomato seedlings - Gemin,Luiz Gabriel (2018)
Looking for the development of products based on natural sources capable of promoting plant growth according to organic production assumptions, the aim of this work was to evaluate the effect of Saccharomyces cerevisiae fermented broth (SFB) as a biofertilizer on organic tomato seedlings growth and chlorophyll content of leaves, taking into account the content of levorotatory configuration amino acids in SFB. For that reason, were performed foliar applications of aqueous solutions with five concentrations (0,25; 0,50; 0,75; 1,0 and 1,25 mL.L-1) of SFB (complex-aid® - Alltech®) and a control with application of distilled water. The SFB showed remarkable efficiency in promoting tomato seedlings growth, increasing leaves chlorophyll content, increasing leaves and stems growth, roots volume and altering its diameter partitioning, improving the rate of thinner roots at 0,75 mL L-1 concentration. These are initial results for further investigations about how SFB acts on plant metabolism, related to L-amino acids or other possible bioactive compounds released by Saccharomyces cerevisiae.